2021
DOI: 10.1080/00224499.2021.1873225
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Functioning, Satisfaction, and Well-Being Among Contraceptive Users: A Three-Month Assessment From the HER Salt Lake Contraceptive Initiative

Abstract: Few large, longitudinal studies document multiple contraceptive methods' effects on sexual functioning, satisfaction, and well-being. We leveraged data from the HER Salt Lake Contraceptive Initiative, a prospective cohort study with patient surveys at baseline, one month, and three months. Surveys assessed bleeding changes, contraceptive-related side effects, sexual functioning and satisfaction, and perceptions of methods' impact on sexual well-being. Individuals in the final sample (N = 2,157) initiated eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
4
5
1
Order By: Relevance
“…Both frequency of sexual activity and sexual enjoyment are positively related to satisfaction with a contraceptive method, as is demonstrated in other studies [44,45]. High standards of satisfaction [44]and a better QoL [46,47] have been described in LARC users who previously have had unwanted pregnancies using a SARC.…”
Section: Intrauterine Devices and Sexualitysupporting
confidence: 69%
See 2 more Smart Citations
“…Both frequency of sexual activity and sexual enjoyment are positively related to satisfaction with a contraceptive method, as is demonstrated in other studies [44,45]. High standards of satisfaction [44]and a better QoL [46,47] have been described in LARC users who previously have had unwanted pregnancies using a SARC.…”
Section: Intrauterine Devices and Sexualitysupporting
confidence: 69%
“…Both frequency of sexual activity and sexual enjoyment are positively related to satisfaction with a contraceptive method, as is demonstrated in other studies [44,45]. High standards of satisfaction [44]and a better QoL [46,47] have been described in LARC users who previously have had unwanted pregnancies using a SARC. Furthermore, Authors observed that women with sexual dysfunction experience significant improvement in sexual desire, arousal, orgasm and overall sexual function while using LNG-IUS.…”
Section: Intrauterine Devices and Sexualitysupporting
confidence: 69%
See 1 more Smart Citation
“…Both frequency of sexual activity and sexual enjoyment are positively related to satisfaction with a contraceptive method, as is demonstrated in other studies [50,51]. High standards of satisfaction [50] and a better QoL [52,53] have been described in IUD users who previously had unwanted pregnancies using a SARC.…”
Section: Intrauterine Devices and Sexualitymentioning
confidence: 54%
“…Both frequency of sexual activity and sexual enjoyment are positively related to satisfaction with a contraceptive method, as is demonstrated in other studies [50,51]. High standards of satisfaction [50] and a better QoL [52,53] have been described in IUD users who previously had unwanted pregnancies using a SARC. Furthermore, authors observed that women with sexual dysfunction experience significant improvement in sexual desire, arousal, orgasm, and overall sexual function while using LNG-IUS.…”
Section: Intrauterine Devices and Sexualitymentioning
confidence: 54%